(3JMaI GdfHjg Ydi cJGH GdJfHjgs - (3eLO GdOjf CHh HcQ Hf ESeGYjd Hf YHO GdYRjR GdRfcdhfjs; (3GdajQhRGHGOj GdTjQGRj , CHh ESMb EHQGgje Hf Ydj GdTjQGRj, CHh GSMGb , LeGd GdOjf,J (B476 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfj deG QCjJ JfHjg ddEeGe GdYdGeI CHj ESMb GdTjQGRj CQOJ Cf CVY Ydjg TQMkG CSdc ajg WQjb GdJhSW s
(3BNQgG (B:s
(3hEPG bJd oYUahQkG heG CTHgg dGjMb Ydjg TGg hbO Sej eG hLH Ydjg gOjkG fLR GdLRA GdChd ef GdJfHjg aj TQM GdJfHjg s
(3GdfSNI HgG MhGTs
(3hgh TQM cHjQ MSf dNUg ef GdQGaYj hGHf GdQaYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B51 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B68s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B490s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs